The Symbolic Meanings of Toraja Carving Motifs - Sofyan Salam; Muh. Saleh Husain Husain; Tangsi Tangsi (LP2M ISBI Bandung, 2017)
ABSTRACTThe study on the symbolic meaning of the Toraja ornamental design was conducted in a traditional wood-carver community at Tonga, Kesu District of North-Toraja Regency. The study question was stimulated by the fact that, nowadays, there are no more wood-carver teachers with tomanarang status (expert in Toraja culture) at Tonga and surrounding areas as there were happened in the past. The method of this study was survey by using indept-interviews technique. The interview was conducted with the traditional wood-carvers at Tonga. The result of study explained that the traditional wood-carvers at Tonga have a meager understanding on the symbolic meaning of the Toraja ornamental-designs. This lack of understanding is caused by the traditional wood-carvers’ view that it is not neccessary to understand the symbolic meaning of the toraja ornamental designs. For them, technical skills in wood-carving are more important to be mastered. The results of the research indicate the occurence of value orientation changes of Toraja wood-carvers.Key words: Wood-carving, symbolic meanings, Toraja ornamental design.ABSTRAKPenelitian makna simbolik motif hias ukir Toraja ini dilaksanakan di sebuah komunitas pengukir-kayu tradisional di Tonga Kecamatan Kesu Kabupaten Toraja-Utara.Pertanyaan penelitian dipicu oleh kenyataan tidak adanya lagi pengukir-kayu yang berstatus tomanarang(ahli ukir dan sekaligus ahli budaya Toraja) di Tonga dan daerah sekitarnya yang berfungsi sebagai guru-ukir sebagaimana yang terjadi pada masa lalu. Metode penelitian ini adalah survey dengan menggunakan teknik wawancara mendalam. Wawancara dilakukan terhadap pengukir-kayu tradisional Toraja yang bermukim di Tonga. Hasil penelitian ini menjelaskan para pengukir-kayu tradisional di Tonga memiliki pemahaman yang amat kurang terhadap makna simbolik dari motif-hias ukir-kayu tradisional Toraja. Kurangnya pemahaman ini disebabkan oleh karena pengukir menganggap tidak perlu memahami makna simbolik tersebut. Bagi mereka, yang perlu dimiliki adalah kemampuan teknis dalam membuat ukiran-kayu. Temuan penelitian ini menunjukkan telah terjadinya perubahan orientasi nilai dari pengukir-kayu tradisional Toraja.Kata kunci: Seni ukir-kayu, makna simbolik, motif hias Toraja